OC-039 Eps8: A Master Regulator of Integrin-Dependent Pancreatic Cancer Invasion. (4th June 2013) - Tod, J; Jenei, V; Chrzan, M; Johnson, C; Fine, D; Thomas, G J
Abstract : Introduction: EGFR pathway substrate 8 (Eps8) is an adapter protein that sits at the heart of a complex system regulating re-organisation of the actin cytoskeleton. Eps8 has been shown to be involved in cell motility and EGFR internalisation, via interactions with multiple intracellular proteins, including integrins. αvβ6 is an epithelial specific integrin, not present in healthy tissue but over-expressed in many carcinomas. αvβ6 promotes tumour invasion and is a key activator of TGFβ, which modulates tumour cell EMT and the desmoplastic response characteristically present in PC. The aim of this study was to investigate whether there is a link between Eps8 and αvβ6 in pancreatic cancer invasion. Methods: We used immunochemistry to examine the expression of Eps8 and αvβ6 in normal pancreas and PC in vivo using tissue microarrays. PC cell motility was investigated using Transwell® assays. siRNA interference was used to down-regulate genes of interest. The ability of PC cells to activate TGFβ was measured using TGFβ-responsive mink lung epithelial cells. Cell surface αvβ6 levels were assessed with FACS analysis. Endocytosis of αvβ6 was suppressed using Clathrin siRNA to examine the role of endocytosis in αvβ6 functions. Pancreatic stellate cells (PSCs) were isolated from primary pancreatic resection tissue and used to optimise 3D pancreatic organotypic cultures. Results: Eps8 and αvβ6 were up-regulated in > 70% PC in vivo but were not generally detected in normal pancreas. An organotypic model of pancreatic cancer was developed using primary PSCs to study αvβ6 functions. αvβ6 promoted PC cell invasion and TGFβ activation. Interestingly, Eps8 knockdown suppressed αvβ6-dependent motility but conversely, promoted αvβ6-dependent TGFβ activation. Although inhibition of αvβ6 endocytosis also increased TGFβ activation, this was not Eps8 dependent, nor did Eps8 knockdown affect total cell surface levels of the integrin. Conclusion: αvβ6 and Eps8 are over-expressed in PC. αvβ6 promotes both invasion and TGFβ activation, and Eps8 appears to act as a molecular switch between these functions. How this relates to disease progression is unclear; in late stage disease, where canonical TGFβ signalling is dysregulated (e.g. SMAD4 mutations which are seen in > 50% of PCs) both αvβ6 functions are likely to be tumour promoting. However, in premalignancy when canonical TGFβ signalling acts as a tumour suppressor, we speculate that up-regulation of Eps8 may result in a pro-invasive phenotype and facilitate tumour development. Eps8 may therefore act as a master regulator of PC invasion by switching the cell function between motility and TGFβ activation at critical time points in PC progression. Disclosure of Interest: None Declared